Intonation and Intensity of President Joko Widodo's Speech - Erwina, Emmy; Alvy Mawaddah; Wardana, Muhammad Kiki (Talenta Publisher, 2025)
This study aims to investigate the prosody of speech by the head of state related to the answer to the question that has recently gone viral and trending is President Jokowi's speech answer to the question on YouTube, with the title